Introduction: Globalization and International Labor Solidarity. Introduction to a Theme - Thörnqvist, Christer (Nordic Journal of Working Life Studies, 2014)
Is cross-national trade union cooperation and labor solidarity a forgotten item on Nordic working life researchers’ agenda? And if so, why? Is not the matter more crucial today than ever, considering the challenges from globalization? True, there have not been too many studies in the field by Nordic scholars, and also true, the field is in great need of research considering the great labor market changes both nationally and globally over the last few decades. In order to find a remedy for this lack, a special workshop was dedicated to the subject at the Nordic Working Life Conference in Elsinore, April 2012. The response among the Nordic academics was not exactly overwhelming, but there were several highly interesting papers, bringing up new aspects or shedding new light on old ones. Some of the papers are now compiled in this special issue of Nordic Journal of Working Life Studies. All of them are individual texts and can be read separately. This introduction is just an attempt to put the articles into their common context, that is, to outline the framework within which they belong by highlighting some items they share (...)